Risk of depression in multiple sclerosis across disease-modifying therapies. (April 2022) - Longinetti, Elisa; Frisell, Thomas; Englund, Simon; Reutfors, Johan; Fang, Fang; Piehl, Fredrik
Background: Depression and use of antidepressants are more common among patients with multiple sclerosis (MS) compared to the general population, but the relation of psychiatric comorbidity to use of different disease-modifying therapies (DMTs) is less clear. Objective: To determine whether risk of incident depression or antidepressant use differed across DMTs, and to assess whether depression and antidepressants affected risk of DMT discontinuation and MS relapses. Methods: We prospectively followed for 8 years a register-based nationwide cohort of 3803 relapsing-remitting MS patients. Results: Patients on rituximab had a lower risk of being diagnosed with depression or initiating antidepressants compared with the reference group treated with interferons (hazard ratio (HR) = 0.72, 95% confidence interval (CI) = 0.54–0.96). Patients diagnosed with depression discontinued interferon treatment to a higher extent than patients without depression (HR = 1.51; 95% CI = 1.15–1.98), as did patients on fingolimod initiating an antidepressant compared to patients who did not initiate an antidepressant (HR = 1.47; 95% CI = 1.04–2.08). Conclusions: Our results indicate that the choice of DMT is associated with subsequent risk of depression in MS, but further studies are needed to establish whether there is a causal link. Overall, depression and use of antidepressants displayed limited associations with DMT discontinuation and MS relapse.